Analysis of Unsafe Act in the Standard Operational Procedures of Injectioning Nurses in Dr. Haryoto General Hospital, Lumajang - Himmah, Elok Faiqotul (Universitas Bondowoso, 2023)
Introduction: Standard Operational Procedures are a set of instructions that have been standardized to meet certain patient needs that aim to direct nursing activities safely in carrying out medical and non-medical actions in order to improve the quality of service through the application of applicable standards. Methode: cross-sectional research design that aims to find out whether there is an influence between the characteristics, knowledge, attitudes and work safety facilities of injecting in the application of Standard Operating Procedures for injecting techniques in efforts to prevent accidents due to needle sticks. The population in this study were 153 people with a total sample of 60 people analyzed using multiple regression. Results: The results showed that 90% of nurses at Lumajang Hospital applied the SPO for injecting according to the multiple regression test found a significant effect between the variables of knowledge on the application of SPO for injecting with a value of ρ value 0.017 <0.05. The largest OR value obtained is 21.106 meaning that the respondent's knowledge has the opportunity 21.106 times in the application of the appropriate SPO and there is a significant influence between the variables of years of service and the application of the SPO with a ρ value of 0.025 <0.05. And the OR value of 17.739 is obtained, meaning that the respondent's tenure has 17.739 opportunities in implementing the correct SOP. Conclusion: It is recommended that there be a firm commitment in implementing SPO as an effort to prevent work-related accidents, develop nurse knowledge through education and training in the field of work safety .